Acid-Catalyzed Synthesis of Biodiesel from Calabash (Crescentia cujete) Seed Oil - Nelson Gaspersz; Matheis F. J. D. P. Tanasale; Chalvin Marco Paula; Mimi Salamawati; Priska Marisa Pattiasina (Postgraduate, University of Mataram, 2026)
This study evaluated the acid-catalyzed production of biodiesel from Calabash (Crescentia cujete) seed oil using sulfuric and nitric acids as transesterification catalysts. Oil extracted by Soxhlet extraction yielded 35.20% and was converted into biodiesel under various reaction conditions to determine the optimum catalyst loading, reaction time, temperature, and oil-to-methanol molar ratio. Sulfuric acid exhibited superior catalytic performance, achieving the highest biodiesel yield of 91.20% at 4% catalyst loading, 65 °C, 4 h, and an oil-to-methanol molar ratio of 1:12. Under optimum conditions, nitric acid produced a lower yield of 65.85% at 3% catalyst loading, 65 °C, 6 h, and a molar ratio of 1:9. GC-MS analysis identified seven methyl esters in the sulfuric acid-derived biodiesel, predominantly methyl hexadecanoate (16.93%), methyl stearate (15.07%), and methyl 9-octadecenoate (43.64%). Biodiesel synthesized using nitric acid contained eight methyl esters, with methyl hexadecanoate (16.55%), methyl stearate (26.90%), and methyl 9-hexadecenoate (21.51%) as the major components. The corresponding burning rates were 1.96 × 10⁻³ and 2.71 × 10⁻³ cm²/s for sulfuric and nitric acid catalysts, respectively. Overall, sulfuric acid proved more effective, producing higher biodiesel yield in a shorter reaction time and demonstrating the potential of C. cujete seed oil as a non-edible biodiesel feedstock.